Validation of the “Hypoglycemia Fear Survey for Parents” in Spanish for the detection of fear of hypoglycemia in parents of children with type 1 diabetes mellitus - Johan Gregorio Reyes Quesada; Cristina Rodríguez de Miguel; Óscar Rey Luque; Teresa Hernández Expósito; Juana Rosa Espino Sánchez; Natalia Rodríguez Novo; María Mercedes Novo Muñoz (Anales de Pediatría (English Edition))
Introduction: Fear of hypoglycemia (FoH) in parents of children with type 1 diabetes mellitus (T1DM) has been described as a barrier that affects the achievement of therapeutic goals and adherence to treatment. Objective: validating the Hypoglycemia Fear Survey for Parents (HFS-P) in Spanish and assessing the relationship between scores and various clinical variables. Methods: We conducted a psychometric analysis of the instrument, evaluating its feasibility, internal consistency, validity and reliability in the intended setting and population. Results: The sample included a total of 149 participants (71.8% mothers). The mean age of the children was 9.9 years (SD, 3.2), with a mean duration of T1DM duration of 3.9 years (SD, 3.5) and a mean glycated hemoglobin (HbA1c) of 7.9% (SD, 1.9). Of all participants, 87.9% reported the use of new technologies for glucose monitoring. The adapted questionnaire consists of 20 items grouped into three dimensions. The Cronbach α for the total scale was 0.92. The HFS-P was significantly correlated to a general worry scale (ρ = 0.47; P < .001). The test-retest reliability analysis showed a strong positive correlation (ρ = 0.84; P < .001). Variables such as family history of T1DM, caregiver educational level, HbA1c level and use of a glucose monitoring system were significantly associated with HFS-P scores. Conclusion: The Spanish version of the HFS-P is a valid and reliable tool that may assist health care professionals in identifying parental FoH and guide the development of interventions aimed at improving disease management in children. Resumen: Introducción: El miedo a la hipoglucemia (MaH) en los padres de niños con Diabetes Mellitus tipo 1 (DM1) se ha descrito como una barrera que influye en el logro de los objetivos terapéuticos y en la adherencia al tratamiento. Objetivo: Validar al español el cuestionario Hypoglycemia Fear Survey for Parents (HFS-P) y establecer relación entre las puntuaciones y distintas variables clínicas. Material y metodo: Se realizó un análisis de las propiedades psicométricas del instrumento (factibilidad, consistencia interna, validez y fiabilidad) en el contexto de destino. Resultados: Participaron 149 sujetos (71.8% madres). La edad de los niños fue de 9.9 ± 3.2 años, con un tiempo de diagnóstico de la DM1 de 3.9 ± 3.5 años y una hemoglobina glicosilada (HbA1c) media de 7.9% ± 1,9. El 87.9% utilizaba nuevas tecnologías para el control de la glucosa. El nuevo cuestionario consta de 20 ítems y 3 dimensiones. El alfa de Cronbach para el cuestionario total fue de 0.92. Se correlacionó el cuestionario con otro sobre la preocupación general (ρ = 0.47; p < 0.001). Para la fiabilidad test-retest, se obtuvo una correlación positiva ρ = 0.84 (p < 0.001). Antecedentes familiares de DM1, nivel académico del cuidador, nivel de HbA1c o sistema de control de glucosa, se asociaron significativamente con las puntuaciones del cuestionario. Conclusion: La versión española del HFS-P se ha mostrado como una herramienta válida y fiable que podría ayudar a los profesionales sanitarios a detectar el MaH de los padres y orientarles en el desarrollo de intervenciones que mejoren el control de la enfermedad del menor.